Literature Review Efektivitas Electronic Word of Mouth terhadap Keputusan Pembelian Konsumen di Media Sosial - Masrikha, Rahma Nur; Anfas, Anfas (Pascasarjana Universitas Muhammadiyah Mamuju, 2024)
The research was conducted to determine the effect of the effectiveness of electronic word of mouth on purchasing decisions on Social Media. The method used in the research is descriptive with the main technique used in this study being a literature review, which attempts to assess the scientific contributions made by various literature sources. The author used databases including Sciencedirect, Research Gate, Google Scholar. The results of the literature research generally present that (e-WOM), can influence consumer purchasing choices on social media. Many studies that present that (e-WOM) significantly influences consumer purchase choices on social media platforms support this conclusion. This impact is mainly related to the externally informed component of purchase decision-making, which is satisfied through (e-WOM).